KAWIN KONTRAK DI KAWASAN PUNCAK Antara Normatif, Yuridis dan Realita - Aidatussholihah, Nurlailiyah (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2012)
The validity of a marriage is based on the compliance of the marital pillars and its requirements. The pillars of marriage are enacted in the compilation of Islamic law. On the other hand, its requirements are enacted both in the compilation of Islamic law and the marriage law no. 1 of 1974. While the prohibited marriage is not known both in the compilation of Islamic law and in the marriage law, fikih, or the Islamic law, discussed the varieties of prohibited marriages, such as the mut’ah marriage. Hence, the prohibition of the mut’ah marriage was being issued between Sunni and Syi’ah until today. In fact, the implementation of the temporary marriage, which has the similarity with the mut’ah marriage especially on its time restriction, can be found at Tugu Utara, Cisarua sub-district, Bogor (Kawasan Puncak). Furthermore, the implementation of the temporary marriage is different either with the mut’ah marriage in Syi’ah or marital norms and purposes in Islam. Finally, this article deals with the contemporary marriage at Puncak in the perspective of Islamic and positive law.[Keabsahan suatu perkawinan didasarkan pada pemenuhan rukun dan syarat nikah. Rukun nikah dibahas dalam Kompilasi Hukum Islam, adapun syarat nikah dimuat dalam Kompilasi Hukum Islam dan Undang-Undang Nomor 1 tahun 1974 tentang Perkawinan. Dalam UUP dan KHI tidak dibahas perkawinan yang dilarang, sementara fikih membahas jenis perkawinan yang dilarang, salah satunya adalah kawin mut’ah. Sampai saat ini keharaman nikah mut’ah merupakan masalah khilafiyah antara Sunni dan Syi’ah. Pada kenyataannya di Desa Tugu Utara Kecamatan Cisarua Kabupaten Bogor (Kawasan Puncak), ditemukan praktik “kawin kontrak”. Praktik kawin kontrak yang berlangsung di Kawasan Puncak tidak sesuai dengan ketentuan nikah mut’ah yang berlaku menurut Syi’ah bahkan bertentangan dengan aturan dan tujuan perkawinan. Tulisan ini mengkaji praktik kawin kontrak di “Puncak” dalam pandangan hukum Islam dan hukum positif.]